O controle de convencionalidade da corte interamericana de direitos humanos nos crimes ocorridos durante as ditaduras militares na América do Sul - Piucco, Micheli (2019)
The Inter-American Court of Human Rights - Inter-American Court of Human Rights, now requires two States Parties, not year 2006, to carry out convention control of the law, making its internal regulations compatible with the American Convention on Human Rights and the interpretation that Court makes. IDH. Diante desse controle, to the IDH Court, to proferiu decisions not related to the Military Decisions and respective Leis of Anistia in South America, invalidating these laws because they considered violating human rights, requesting that the States seek an internal adequacy of human rights treaties and treaties. investigassem, julgassem e punissem os responsáveis for serious violações to human directs committed in these periods and sheltered hair véu da impunidade destas leis. A problematic to work and investigate from the control of conventionality exercised by the Inter-American Court of the two States of Chile, Brazil and Uruguay, not related to the military and respective invalidity of the law of anistia, these States that are condemned in international arena, will comply with the decision of the Inter-American Court. With the two States mentioned above, some of them will partially respect the decisions of the Inter American Court of Human Rights, and will continue to contradict the international responsibility issued. Além disso, cases like or da Argentina reflect that or control of conventionality can also be exercised in a prevent ive manner, not carrying or international status of the State. Two days before the InterAmerican Court, various questões surgem, as to what surrounds national sovereignty, to democracy in the IACHR Court and in the absence of efficiency in their judgments. Different objectives, specific objectives for the realization of a historical record on the control of conventionality, to analyze two paragraphs for the IDH Court concerning cases related to the respective military laws of South America and the avaliação do exercício desse controle halos internationally held responsible. In the case of research, it is possible to conclude that the States analyzed will partially comply with certain reparations, since Chile and Uruguay have alternatives to the inapplicability of their laws of anistia, as Brazil is stagnating. As a conventional control exercise, the States seek to make efficient use of human rights treaties, granting cases in an analysis, or directing to justification, in memory and in real cases, and to all societies. In the inter-American sphere, the States must evolve and develop issues of guarantee and protection of human rights, which also depend on an international environment of guarantee, protection and internal efficiency.